Made in Medellin. (Medellin : City of Medellin, 1989)
Aristizabal, Jorge ; Bernal, Adolfo ; Bouhot, Flor Maria ; Castro, Luz Elena ; Gilmour, Ethel ; Group of Architects ; Gonzalez, Alberto ; Jaramillo, Beatriz ; Jaramillo, Oscar ; Marin, Alvaro ; Mesa, Juan Luis ; Montoya, Armando ; Pelaez, Luis Fernando ; Piedrahita, Hilda ; etc.
Made in Medellin, International Monetary Fund Visitors Center, Washington, October 4 - November 10, 1989 ; Herter Art Gallery, University of Massachusetts, Amherst, Massachusetts, December 4 - 22, 1989 ; President's Gallery, Massachusetts College of Art, Boston, Massachusetts ; etc.
Engels
kunstcatalogus
Keywords: Medellin